Proteomics of stress responses in wheat and barley-search for potential protein markers of stress tolerance - Kosová, Klára; Vítámvás, Pavel; Prášil, Ilja T (Frontiers in plant science, 2014)
Wheat (Triticum aestivum; T. durum) and barley (Hordeum vulgare) agricultural production is severely limited by various abiotic and biotic stress factors. Proteins are directly involved in plant stress response so it is important to study proteome changes under various stress conditions. Generally, both abiotic and biotic stress factors induce profound alterations in protein network covering signaling, energy metabolism (glycolysis, Krebs cycle, ATP biosynthesis, photosynthesis), storage proteins, protein metabolism, several other biosynthetic pathways (e.g., S-adenosylmethionine metabolism, lignin metabolism), transport proteins, proteins involved in protein folding and chaperone activities, other protective proteins (LEA, PR proteins), ROS scavenging enzymes as well as proteins affecting regulation of plant growth and development. Proteins which have been reported to reveal significant differences in their relative abundance or posttranslational modifications between wheat, barley or related species genotypes under stress conditions are listed and their potential role in underlying the differential stress response is discussed. In conclusion, potential future roles of the results of proteomic studies in practical applications such as breeding for an enhanced stress tolerance and the possibilities to test and use protein markers in the breeding are suggested.
Keywords: barley; wheat; abiotic stress factors; biotic stress factors; protein markers; proteome